Literasi Digital dan Etika Penggunaan Artificial Intelligence untuk Siswa Sekolah Menengah Kejuruan - Argha Orion Silitonga; Debby Erce Sondakh; Raissa Maringka; Jacquline Waworundeng; Lidya Chitra Laoh (Universitas Klabat, 2026)
This Community Service Program (PKM) conducted by the Faculty of Computer Science at Universitas Klabat aims to enhance digital literacy and understanding of Artificial Intelligence (AI) ethics among students of SMK Negeri 1 Ratahan. Using a participatory-educational approach, the program includes interactive seminars, group discussions, case study analysis, and demonstrations of AI technologies and Large Language Models (LLM). Participants gained knowledge of basic AI concepts, ethical principles such as fairness, transparency, and accountability, as well as the social implications of AI usage. Evaluation results indicate a significant improvement in students’ understanding and awareness of AI ethics, reflected through post-test outcomes and participant feedback. The program not only broadened students’ technological insights but also fostered critical thinking and responsible digital behavior. This initiative is expected to serve as a foundation for continued collaboration between the school and higher education institutions in strengthening digital literacy and AI ethics education at the vocational secondary level.